Characteristics and Title Keywords of Teaching Practice Research Projects Driven by Open Data - Chih-Lin Chung; Wei-Che Hsu (National Taipei University of Education, 2023)
The Ministry of Education (MOE) recently initiated a teaching practice research (TPR) program for higher education which has drown participation of professors from 152 universities. The present data-driven study utilized the open data of 3,699 TPR projects from 2018 to 2020. The dataset includes project titles, disciplines, and information about applicants' positions and affiliations. This research employed statistical analysis to identify TPR characteristics and issues, adopted text mining techniques to explore title keywords, and provides insights into the future development of TPR. This study represents Taiwan's first macroscopic investigation on TPR, which could benefit instructors' project applications, universities' planning of TPR training programs, and MOE's policy-making. The results reveal the following key findings: 1) The participation rate of full-time faculty members in the TPR program is low, with only 5-7 out of 100 faculty members applied and a further 2-3 being approved. Associate and assistant professors are the main contributors to TPR projects, and there is a similar project participation rate between applicants from public and private universities. Comprehensive and vocational universities targeted different TPR disciplines. While seven disciplines experienced an increase in project approval rate, five disciplines did not. Common issues identified include budget constraints and a lack of journal publishing opportunities for TPR reports. Participation rates also varies across individual disciplines and universities. 2) 14 sets of high-frequency terms, or quasi-keywords, in four categories were identified: (a) (learning) effectiveness and motivation for research targets; (b) integration, innovation, and cross-disciplinary for project highlights; (c) listening-speaking-reading-writing skills, thinking, programming, and literacy for learning competencies; and (d) project/problem-based learning (PBL), digital, flipped, cooperative learning, and gamification for pedagogical approaches.